1976
DOI: 10.1111/j.1476-5381.1976.tb07697.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphine–naloxone Interaction in the Central Cholinergic System: The Influence of Subcortical Lesioning and Electrical Stimulation

Abstract: I The opiate antagonist naloxone, injected or topically applied to the cerebral cortex, had no significant effect on the spontaneous output of cortical acetylcholine (ACh) in rats. 2 Morphine (2.5 mg/kg) administered intravenously inhibited the release of cortical ACh. A subsequent injection of naloxone rapidly reversed morphine-induced inhibition, and produced a sustained increase in the release of ACh. Topical application of naloxone solutions, after morphine, produced a slow and weak reversal of its inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Experiments were performed on Sprague-Dawley rats (250 to 300 g) lightly anaesthetized with a mixture of pentobarbitone and urethane (Jhamandas & Sutak, 1976). The spontaneous release of cortical ACh, in the presence of neostigmine (50 mg/ml) and atropine (0.8 mg/ml), was measured by the cup technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were performed on Sprague-Dawley rats (250 to 300 g) lightly anaesthetized with a mixture of pentobarbitone and urethane (Jhamandas & Sutak, 1976). The spontaneous release of cortical ACh, in the presence of neostigmine (50 mg/ml) and atropine (0.8 mg/ml), was measured by the cup technique.…”
Section: Methodsmentioning
confidence: 99%
“…The reversal of morphine (Jhamandas & Sutak, 1976), methadone and levorphanol (Jhamandas, Hron & Sutak, 1975) by naloxone is always complete and it is associated with a large overshoot. In contrast, the reversal of Met-enkephalin by naloxone at similar doses is often incomplete and it is not associated with an overshoot phenomenon (Jhamandas et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Vasko & Domino (1976) showed that morphine at a low dose (1 mg/kg s.c.) increased locomotor activity and, concomitantly, increased ACh utilization in the thalamus. Moreover, Jhamandas & Sutak (1976) found that naloxone, either alone or after morphine, facilitated the increase of cortical ACh release caused by medial thalamus stimulation. Morphine and enkephalins did not modify resting ACh release in any area tested (Szerb, 1974;Vizi et al, 1977).…”
Section: Discussionmentioning
confidence: 96%
“…This effect which is prevented by naloxone (Jhamandas, Phillis & Pinsky, 1971;Jhamandas, Hron & Sutak, 1975;Beani, Siniscalchi & Sarto, 1979;Domino, 1979;Jhamandas & Sutak, 1980), may be due to an action on subcortical sites, since it is abolished by lesions of the medial thalamus or septum (Jhamandas & Sutak, 1976;Pepeu, Garau, Mulas & Marconcini-Pepeu, 1975).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation